PEMETAAN KERENTANAN GERAKAN MASSA TANAH DAN BATUAN SEKITAR DESA PENDOWOREJO, KECAMATAN GIRIMULYO, KABUPATEN KULONPROGO, YOGYAKARTA - , AULIA HIDAYAT. B; , Dr.Wahyu Wilopo, S.T., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kulon Progo is an area with high and mountainous terrain morphology with high level of vulnerability of ground mass movement. The study was based on an interest in morphological conditions of the mass movement that can occur, especially during the rainy season where abundant amount of water greatly affects the activity of the mass movement. This research focused on creating a vulnerability map based on several parameters that influence it, such as the slope parameter, the distribution of lithology, geological structure, surface sediment type, and land use. Regional research unit composed of andesite lava, breccia unit autoclastic, then units of koluvium unconformity sedimented on the units of alluvium. The main control parameter in the study area is the slope parameter. Study area was divided into 3 level zones of vulnerability, high level of vulnerability zones, moderate level of vulnerability zones, and low level of vulnerability zones. Areas with high levels of vulnerability include Penggung, Ngliweng, Pendoworejo. From these results, there are some managements that can be done by governments and local citizen, such as creating a more sloping cliffs with terraces, making the rock barrier at the foot of slope in case ground mass movements come off, makes drainage to reduce water infiltration into the slope, build a concrete retaining wall on the steep cliffs, and give the patio as the distance between the buildings with steep slopes.